Do different factors explain male and female self-employment rates? - Saridakis, George; Marlow, Susan; Storey, David J. (Journal of Business Venturing, 2014)
This article challenges the assumption that the factors associated with the self-employment choices of women differ from those of men; specifically, we test the extent to which women are influenced by standard economic factors compared with family and social issues. We find that economic factors influence the self-employment choices made by men and by women in the long and short-run. Although some findings were sensitive to the chosen self-employment measure our short-run findings, in particular, are at variance with the interpretation that self-employed women are less likely to be influenced by economic factors than their male counterparts. Consequently, we argue that gender-based explanations have exaggerated the importance of social factors in the self-employment choices made by women.